Phytochemical Screening and Blood Glucose Level Effects of Bhee Fruit Extract (Melastoma sp) on Diabetic Mice - Rinawati, Rinawati; Muhsin, Sri Wahyuni; Sari, Widia; Hayuningtyas, Afwa; Putri, Suci Eka; Nursia, Lili Eky; Fitri Siregar, Siti Maisyaroh (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
Diabetes is a non-communicable disease among the highest causes of death worldwide, including in Indonesia. Factors that cause diabetes include pancreatic β-cell damage, genetic factors, and an unhealthy lifestyle. Diabetes is characterized by high blood glucose levels (hyperglycemia) beyond normal limits. Hyperglycaemia can be treated using synthetic chemical drugs or insulin therapy, which has adverse long-term effects. The community believes herbal medicine is an alternative diabetes treatment. Melastoma sp is a plant that has the potential as an antidiabetic agent. This study aimed to determine the effectiveness of ethanol extract of Bhee fruit (Melastoma sp) on blood glucose levels of diabetic mice. This study is a laboratory experiment using laboratory animals. The mice were divided into seven treatment groups with three replicates: KN (normal control), KP (treatment control), KD (diabetes control), KO (drug control), P1 (treatment dose of 100 mg/kgBB extract), P2 (treatment dose of 200 mg/kgBB extract), and P3 (treatment dose of 400 mg/kgBB extract). The study's results, the administration of doses of ethanol extract of the fruit 100, 200, and 300 mg /kgBB for 14 days reduced glucose levels in diabetic mice. However, they could not exceed the ability metformin at a dose of 500 mg/kgBB.